2014
DOI: 10.1371/journal.pone.0086051
|View full text |Cite
|
Sign up to set email alerts
|

Mining Gene Expression Data for Pollutants (Dioxin, Toluene, Formaldehyde) and Low Dose of Gamma-Irradiation

Abstract: General and specific effects of molecular genetic responses to adverse environmental factors are not well understood. This study examines genome-wide gene expression profiles of Drosophila melanogaster in response to ionizing radiation, formaldehyde, toluene, and 2,3,7,8-tetrachlorodibenzo-p-dioxin. We performed RNA-seq analysis on 25,415 transcripts to measure the change in gene expression in males and females separately. An analysis of the genes unique to each treatment yielded a list of genes as a gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 100 publications
6
45
1
Order By: Relevance
“…The microarray analysis showed that inhalation of both toluene (1,000 μg/m 3 ) and formaldehyde (100 μg/m 3 ) for 24 h was sufficient to induce genome-wide gene expression changes in Drosophila . The GO and pathway analyses for DEGs identified GO terms or pathways similar to those previously reported in a murine model including GO terms of immune response, xenobiotic metabolism, neurological system process, and pathways related to the cellular stress response such as NF-κb, PI3K, and p38 MAPK pathways151617181920. This indicated that the inhalation of toluene and formaldehyde induced similar cellular responses in Drosophila compared to those in mammals.…”
Section: Resultssupporting
confidence: 69%
“…The microarray analysis showed that inhalation of both toluene (1,000 μg/m 3 ) and formaldehyde (100 μg/m 3 ) for 24 h was sufficient to induce genome-wide gene expression changes in Drosophila . The GO and pathway analyses for DEGs identified GO terms or pathways similar to those previously reported in a murine model including GO terms of immune response, xenobiotic metabolism, neurological system process, and pathways related to the cellular stress response such as NF-κb, PI3K, and p38 MAPK pathways151617181920. This indicated that the inhalation of toluene and formaldehyde induced similar cellular responses in Drosophila compared to those in mammals.…”
Section: Resultssupporting
confidence: 69%
“…Sample preparation and RNA sequencing were carried out by previously used protocol with modifications [6, 7]. The Illumina TruSeq™ RNA Sample Preparation Kit (Low-Throughput protocol) was used to prepare samples for mRNA sequencing libraries.…”
Section: Methodsmentioning
confidence: 99%
“…A search for latent correlations in the time series of data, related to the chemiluminescence intensity, was performed by the method of detrended fluctuation analysis (DFA) [39] with a modification [40]. In this method, the fluctuation function Fd(l) is plotted in accordance with equation:…”
Section: Methods Of Detrended Fluctuation Analysismentioning
confidence: 99%
“…The wavelet transform of the time series {Xi}of the luminescence intensity values makes it possible to reveal the amplitude-frequency and phase-frequency characteristics of signals locally with time [40]. The result of the wavelet transform represents the expansion of the time series {Xi} over the basis of soliton-like functions (the so-called Morlet basis): …”
Section: Wavelet Transformmentioning
confidence: 99%